Characteristics of Child Maltreatment and Adolescent Marijuana Use: A Prospective Study. (February 2016) - Dubowitz, Howard; Thompson, Richard; Arria, Amelia M.; English, Diana; Metzger, Richard; Kotch, Jonathan B.
There has been increasing acceptance of marijuana use in the United States in recent years, and rates among adolescents have risen. At the same time, marijuana use during adolescence has been linked to an array of health and social problems. Maltreated children are at risk for marijuana use, but the relationships among characteristics of maltreatment and marijuana use are unclear. In this article, we examine how the type and the extent of maltreatment are related to the level of adolescent marijuana use. Data analyses were conducted on a subsample of maltreated adolescents ( n = 702) from the Longitudinal Studies of Child Abuse and Neglect project. Approximately half the sample had used marijuana, and maltreatment was associated with its use. Multivariate regression models showed that being male, extensive maltreatment, and peer marijuana use were associated with heavy use of marijuana. These findings suggest the importance of comprehensively assessing children's maltreatment experiences and their peers' drug use to help prevent or address possible marijuana use in these high-risk adolescents.